Interplay of physical activity, self-rated health, and life satisfaction among large-bodied adolescents in Europe and North America: analysis using clustered binary mixed effects logit modelling - Michael Safo Oduro; Eniola Fasola; Prince Peprah; Isaac Yeboah Addo (BMC Public Health)
Abstract Background There is a dearth of studies focused on the impact of self-rated health on life satisfaction among large-bodied adolescents, as well as the moderating role of physical activity in this relationship. Large-bodied adolescents refers to young people (usually aged 10–19 years) whose body size falls within the overweight or obese range as defined by the World Health Organisation’s Growth Reference, based on age- and sex-specific body mass index (BMI) percentiles. This study aimed to address the gap in research by examining the association between self-rated health and life satisfaction in a diverse sample of large-bodied adolescents from 39 countries and regions in Europe and North America. The moderating role of physical activity in the association was also examined. Methods The study analysed data from the Health Behaviour in School-aged Children (HBSC) survey, involving a sample of 24,839 large-bodied adolescents. Three sequential binary mixed effects logit models were fitted: the first assessing self-rated health alone, the second adjusting for multiple covariates, and the third incorporating an interaction term between physical activity and self-rated health. The analysis was performed using R Software (v4.1.2), with significance determined at a level of 0.05. Results The results show that adolescents who rated their health as “poor” were a little more than six times (AOR = 6.32, 95%CI: 5.30–7.54, p < 0.001) as likely to report lower life satisfaction compared to those who rated their health as “excellent”. Those who rated their health as “good” had 1.71 times higher odds (AOR = 1.71, 95%CI: 1.44–2.04, p < 0.001) of reporting lower life satisfaction compared to those who rated their health as “excellent”. The analysis further indicated that physical activity plays a partial moderating role in the relationship between self-rated health and life satisfaction. Participants who considered themselves “somewhat active” reported higher life satisfaction compared to their “inactive” peers (AOR = 0.58, p = 0.031, 95% CI: 0.36–0.95). Conclusions The study supports the hypothesis that poorer self-rated health is associated with lower life satisfaction among large-bodied adolescents. It further suggests that increased physical activity can ‘partly’ buffer the negative effects of poor self-rated health on life satisfaction. These findings emphasise the importance of interventions promoting physical activity and positive self-care to improve general well-being in large-bodied adolescents.